(untitled) (Indian Journal of Arid Horticulture, 2025)
Combining ability analysis was carried through diallel mating design (excluding reciprocals) involving eight parents for fourteen characters. The analysis revealed highly significant differences among the genotypes for all the parameters studies. The variances due to sca were higher than the gca for vine length, days to first fruit harvest, harvest duration, fruit length, average weight of first three harvested fruits, number of marketable fruits, fruit yield per plant, size of seed cavity and flesh thickness indicating the predominance of non-additive gene effects. None of the parents was found good general combiner for all the characters consistently, however, parent Pusa Naveen, NDBG-104, NDBG-140, and Bharatpur Local showed higher combining ability for yield and yield attributing traits. The best specific cross for days to first female flower and days to first fruit harvest was Pusa Naveen x NDBG-132 and Pusa Naveen x RS-1, respectively. The crosses Pusa Naveen x NDBG-104 and Pusa Naveen x UL-6 were identified as best specific combiners for average weight of first three harvested fruits, number of marketable fruits and fruit yield per plant.